THE EFFECT OF BIBLIOTHERAPY TO IMPROVE YOUTH'S KNOWLEDGE AND ATTITUDES ABOUT BULLYING IN THE DIPONEGORO ORPHANAGE - Widayati, Ririn Wahyu; Lestiawati, Endang; Wijaya, Febriani Melison (Universitas Respati Yogyakarta, 2021)
Adolescents have an egotistical nature whose desire to be the center of attention, one way is by bullying. The purpose of this study was to see the effect of bibliotherapy on adolescent knowledge and attitudes about bullying at the Diponegoro Orphanage, Yogyakarta. This type of quasi-experimental research with pre-test and post-test nonequivalent control group. The sampling technique was total sampling, 40 respondents who were divided into the control group and the intervention group. The instrument used was a knowledge and attitude questionnaire and a novel for bibliotherapy. The results of the knowledge level in the group that were found at the time of the pre-test were good knowledge of 60% and the post-test was 55%, while the results of the knowledge level in the intervention group were found at the pre-test with good knowledge of 55% and the post-test. at 100%. The results of attitudes in the control group were obtained during the pre-test, namely a positive attitude of 10% and a post-test of 5%, while the results of the attitude description in the intervention group were found during the pre-test, namely a positive attitude of 15% and a post-test of 5%. 85%. The results of the McNemar test for the knowledge control group were 1,000, while the intervention group was 0.004. The attitude in the control group was 0.625, while in the intervention group the results of the observation were 0.002. There is an effect of bibliotherapy on the level of knowledge and attitudes about bullying in adolescents. Keywords: Attitudes; Bibliotherapy; Bullying; Knowledge